Assessment of components of crack users' attention network - Leandro Barbosa de Pinho; Christine Wetzel; Jacó Fernando Schneider; Agnes Olschowsky; Marcio Wagner Camatta; Eglê Rejane Kohlrausch; Cintia Nasi; Adriane Domingues Eslabão; Elitiele Ortiz dos Santos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Assess components of the Psychosocial Attention Network (RAPS) in crack user care in a Rio Grande do Sul municipality. Method: Qualitative study based on Fourth Generation Evaluation. Data collection occurred in 2014, through participating observation and interviews based on the Hermeneutic-Dialectic Circle. Ten uses, eleven family members, seven managers and eight workers at a Psychosocial Attention Center participated. The Constant Comparative Method was used for data analysis. Results: Difficulties were observed in the network articulation with the general hospital, due to prejudice and the lack of structure of the team. SAMU's (Mobile Emergency Care Service) dependence on the Military Brigade for the service indicates a frailty of the network. The need to re-think the way therapeutic farms operate in the network is a consensus. Conclusion: RAPS is being implemented and its concretization depends on the involvement of professionals, managers and social control of users and family members.